A Bioenergetics Approach to Assessing Potential Impacts of Avian Predation on Juvenile Steelhead during Freshwater Rearing. (25th September 2013) - Frechette, Danielle; Collins, Alison L.; Harvey, James T.; Hayes, Sean A.; Huff, David D.; Jones, Andrew W.; Retford, Nicolas A.; Langford, Alina E.; Moore, Jonathan W.; Osterback, Ann‐Marie K.; Satterthwaite, William H.; Shaffer, Scott A.
Abstract: Avian predation on juvenile salmonids is an important source of mortality in freshwater and estuarine habitats when birds and salmonids overlap spatially and temporally. We assessed the potential impact of avian predation upon juvenile steelhead Oncorhynchus mykiss in a coastal watershed in central California. We conducted stream surveys between 2008 and 2010 to determine the composition, distribution, and density of piscivorous birds in areas that provide rearing habitat for juvenile steelhead. The most commonly sighted bird species were common mergansers Mergus merganser and belted kingfishers Megacyrle alcyon . The density of avian predators varied spatially and temporally but was greatest in the estuary regardless of season and decreased with increasing distance from the estuary. In the absence of local predator diet data, we applied a bioenergetics model to estimate the potential predation on juvenile steelhead by mergansers and kingfishers in the Scott Creek estuary. Model parameters included (1) published values of bird energetic requirements and steelhead energy density, (2) the number of birds present in the estuary during the closure period (from stream surveys), and (3) the size frequency and abundance of steelhead present in the estuary during closure. We predicted the extent of predation for different values of steelhead in bird diets, accounting for uncertainty in the estimates using a Monte Carlo simulation approach. With the assumed contribution of steelhead to the diet ranging from 20% to 100%, the population of kingfishers foraging in the Scott Creek estuary had the potential to remove 3–17% of annual production, whereas mergansers had the potential to remove 5–54% of annual steelhead production. Our results suggest that predation by avian species, particularly mergansers, is an important source of mortality for threatened steelhead populations in central California and should be addressed in future salmonid research and recovery planning. Received February 13, 2013; accepted June 4, 2013